Validitas Modul Ekologi Berdasarkan Hasil Identifikasi Jenis Bintang Laut (Asteroidea) - Khairunnisah, Khairunnisah (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2024)
Modules can help educators achieve quality learning. The application of modules can condition learning activities to be more well planned, independent, complete, and with clear results (output). This research aims to test the feasibility of the ecological module based on the results of identifying types of sea stars (Asteroidea). The type of research used is development research. The research sample used was 15 students of the Department of Biology Education, Faculty of Applied Science and Engineering, Mandalika University of Education. Data collection techniques include validation and readability testing. The data analysis technique used is the percentage technique. Based on the research results, it was explained that the development of the ecology module was validated by a team of experts (material, language and appearance), and the student readability test obtained an average of 74.1% and the readability test was 87.8%. It was concluded that the ecological module developed was declared quite valid without needing revision and was very readable.